The contemporary faith in educational technology – a critical perspective - Player-Koro, Catarina (Tidsskrift for Professionsstudier, 2016)
The purpose of this article is to contribute to the discussion about the contradictions between the optimistic faith in improving education through the implementation of technology and the actual realities of educational use of technology. This is done through a summary and overview of the results of three different studies in the field of educational technology that started in 2005 and that is still on going. The aim of these studies has been to contribute to development of a critical perspective on educational technology and thereby contribute to knowledge development about education of today.